The troubling state of nuclear controls. - Sweet, W.
A decade after the cold war officially ended-with the reunification of Germany, the liberation of Eastern European nations from Soviet hegemony, and the collapse of the Soviet State itself-events have taken an alarming turn for the worse. The United States and Russia have refused to ratify nuclear arms control treaties they signed, both are back-pedaling on the implementation of less formal arms agreements, and they are bickering over a broad range of issues on which their differences are widening rather than narrowing. The authors discuss these issues and what can be done to overcome the problems and eliminate the nuclear menace
Keywords: Russia; United States; Arms agreements; Cold war; Nuclear arms control treaties; Nuclear controls